Lactate-induced protein lactylation in cancer: functions, biomarkers and immunotherapy strategies - Wang, Wenjuan; Wang, Hong; Wang, Qi; Yu, Xiaojing; Ouyang, Liangliang (Frontiers in Immunology, 2025)
Lactate, long viewed as a byproduct of glycolysis and metabolic waste. Initially identified within the context of yogurt fermentation, lactate’s role extends beyond culinary applications to its significance in biochemical processes. Contemporary research reveals that lactate functions not merely as the terminal product of glycolysis but also as a nexus for initiating physiological and pathological responses within the body. Lysine lactylation (Kla), a novel post-translational modification (PTM) of proteins, has emerged as a pivotal mechanism by which lactate exerts its regulatory influence. This epigenetic modification has the potential to alter gene expression patterns, thereby impacting physiological and pathological processes. Increasing evidence indicates a correlation between lactylation and adverse prognosis in various malignancies. Consequently, this review article aims to encapsulate the proteins that interact with lactate, elucidate the role of lactylation in tumorigenesis and progression, and explore the potential therapeutic targets afforded by the modulation of lactylation. The objective of this review is to clarify the oncogenic significance of lactylation and to provide a strategic framework for future research directions in this burgeoning field.